AGAMA FORMAL VS KECERDASAN SPRITUAL (ANALISIS KONSELING SPRITUAL TERHADAP FENOMENA KORUPSI) - Devi Adriani (IAIN Padangsidimpuan, 2017)
Corruption is a negative action that a person undertakes to gain his own advantage. Not infrequently corruption is done by someone who has a high education and religion. Formal religion is a set of externally charged rules and beliefs. It is top-down, inherited from priests, prophets and scriptures or inculcated through family and tradition. Spiritual intelligence is the intelligence to deal with and solve the problem of meaning and value, the intelligence to gain behavior and live in the context of broader and more rich meaning, the intelligence to judge that one's actions or way of life are more meaningful than others. spiritual intelligence can not be equated with religion. Although some people improve spiritual intelligence through religious approach. But that does not mean people are not religious can not have high spiritual intelligence. Counseling approach to the phenomenon of corruption is spiritual counseling with the method of counselor prayer, then giving information about spiritual concepts, referring to scripture, spiritual disclosure, spiritual confrontation, prayer with counselor and counselee, encouragement, use of community or religious group , counselee prayer and religious bibilioterapi.Keywords: corruption, formal religion, spiritual intelligence,spiritual counseling